Pemeliharaan dan Pengendalian Pencegahan Infeksi Rekam Medis COVID-19 oleh Petugas Rekam Medis - Nina Rahmadiliyani Rahmadiliyani; Najla Shaffiya Putri (HB PRESS, 2021)
The coronavirus can last between four and five days in various objects aluminum, wood, paper, plastic, and glass objects. It is spread through paper (especially medical record documents) and still becoming a risk. Maintenance of COVID-19 medical records had not been carried out according to the PORMIKI’s instructions. The records were not put in plastics or containers and not stored in a special place. This study aimed to determine the maintenance and control of COVID-19 infection prevention by medical record officers in 2021. This study used a qualitative descriptive method. The main informants were coding officers, and the triangulation informants were the head of the medical record installation and the isolation room administration officer. The research instruments were observation and interview guidelines. We used descriptive analysis. The results showed that Standard Operational Procedure (SOP) of the COVID-19 medical records maintenance at Idaman Hospital, Banjarbaru, was not yet available. The observation results showed that the officers obeyed to wear masks during working, wash hands routinely using hand rub, clean the tables or other flat surfaces before and after working, and minimize the contact between patients or their families and medical records. However, some procedures were not carried out (e.g., did not put the medical records in yellow plastics, container boxes, or a special place. The hospital should make an SOP regarding the maintenance of medical records for COVID-19 patients that the officers should comply with and anticipate the potential for workers to have COVID-19.